2012
DOI: 10.4103/0019-5413.101039
|View full text |Cite
|
Sign up to set email alerts
|

Use of amplified Mycobacterium tuberculosis direct test (Gen-probe Inc., San Diego, CA, USA) in the diagnosis of tubercular synovitis and early arthritis of knee joint

Abstract: Background:The diagnosis of knee joint tuberculosis, especially in early stages of synovial disease, has more often been based on clinicoradiological suspicion, with no single test claiming to be a dependable rapid diagnostic test with high sensitivity and specificity. Nuclear amplification tests in vogue like the polymerase chain reaction have shown variable sensitivity and false positivity rates in various studies. We evaluated the role of Amplified Mycobacterium tuberculosis Direct Test (AMTDT) or Genprobe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…8 PCR for TB diagnosis has gained popularity firstly for its rapid yield of results, usually within hours in well-organized centres. 7,8,10,14 Secondly the sensitivity to Rifampicin is determined relatively fast, versus in MC&S. 10 For synovial fluid in osteoarticular TB, PCR sensitivity for diagnosis was reported at (63%) by Aggarwal et al 11 The latter figure is similar to the one in our study (63%) it is well within a range from 32 to 78% that is reported in the literature. 7,8 There has been a reported further improvement with a modified version of PCR namely, the Nested type.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…8 PCR for TB diagnosis has gained popularity firstly for its rapid yield of results, usually within hours in well-organized centres. 7,8,10,14 Secondly the sensitivity to Rifampicin is determined relatively fast, versus in MC&S. 10 For synovial fluid in osteoarticular TB, PCR sensitivity for diagnosis was reported at (63%) by Aggarwal et al 11 The latter figure is similar to the one in our study (63%) it is well within a range from 32 to 78% that is reported in the literature. 7,8 There has been a reported further improvement with a modified version of PCR namely, the Nested type.…”
Section: Discussionsupporting
confidence: 86%
“…based on adequate history taking, clinical examination, and/or typical radiological changes. 11,12 Naturally, high-index cases would then be treated empirically based on a clinical impression suggestive of osteoarticular TB diagnosis. 8 However, this practice has lost favour due to an upsurge in cases of drug-resistant TB, therefore, fostering a need for drug sensitivity analysis to be determined before initiation of any anti-TB chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, nucleic acid-based amplification (NAA) tests have emerged as important tools for diagnosing TB. Unfortunately, these tests have a high specificity (100%) but low sensitivity (32%-78%) [11][12][13]. In our patient, the first PCR test was negative, perhaps due to the small volume extracted (3 mL).…”
Section: Discussionmentioning
confidence: 67%
“…The use of interferon-gamma release assay (IGRA) has recently shown promising results in diagnosing active extrapulmonary TB [10][11][12][13][14], with a sensitivity of 67%-93% and a specificity of 69%-78% on peripheral blood samples [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 , 12 ]. In the case of synovial fluid, PCR tests have shown moderate sensitivity (63%) but excellent specificity (92–100%) [ 13 ]. Thus PCR tests are a useful and very convenient test for OA-TB, but synovial biopsy should be performed in patients with a negative test.…”
Section: Discussionmentioning
confidence: 99%